Awareness and Perceptions of Islamic Micro-Entrepreneurs on Mudharabah Finance and Justice for Financing Access in Malang Territory Indonesia - Suhendri, Hendrik; Triyuwono, Iwan; Mulawarman, Aji Dedi; Baridwan, Zaki (International Journal of Economics and Financial Issues, 2017)
Micro Business becomes one of the backbone of the Indonesia national economy. Besides to most of the workforce has been absorbed by this sector. In the midst of the instability of the price of basic commodities, fuel, and the application of a one percent tax on sales turnover from MSMEs, it is necessary for other compensation for micro business to be given ease in accessing financing in Islamic banking. The research was to understand the Islamic Micro-Entrepreneurs (IME) understanding of the products of Mudharabah financing. It also wants to know the perception of IME related access to financing in Islamic banking. The results of this study indicate that the IME lack an understanding and familiarity with the products of mudharabah financing. In fact they felt that financing is the same as a regular credit financing. In addition mostly respondents convey disapproval or feel treated unfairly, when IME access the Islamic banks finance. Keywords: Micro Small Medium Enterprises (MSMEs), Islamic Micro-Enterpreneurs (IME), Mudharabah Financing, Islamic Banks. JEL Classifications: D63, G21, G32, M21